Behavior of Ni in ZnO/Al working electrode for K+ ion sensor - panda, Usharani; Das, Arun K.; Ali, Farida A.; Pattanaik, Priyabrata; Kamilla, Sushant K. (International Journal of Psychosocial Rehabilitation, 2020)
Ni doped ZnO has been widely studied as a diluted magnetic semiconductor (DMS), but in this work we have shown its use as a biosensor. To analyze biological samples, it is required to convert the biological events to an equivalent electrical output, which is done by electrochemical biosensors at an affordable price.Alkali metal ions play a vital role in biological events and study of which is necessary to know the healthy functioning of human body organs. Potassium ion (K+) is one of the alkali metal ion in blood which needs regular monitoring. This was a motivating factor for us to go for the fabrication of working electrodes like ZnO coated on Al substrate (ZnO/Al) and Ni doped ZnO coatedon Al substrate (Ni in ZnO/Al)in sol–gel method by Chemically Wet and Dry technique (CWD), an indigenous method that has been developed in our lab.The fabrication process was followed by in-situ annealing of the sample electrodes at 450°C in presence of Nitrogen environment. The crystalline property of the synthesized materials was confirmed by XRD study. The Hall Effect study shows higher mobility and conductivity values for Ni doped ZnO in comparison to pure ZnO. The pH level variations for various concentration of KOH solution were studied by both electrodes separately considering Ag as reference electrode.The sensitivity of Ni in ZnO/Al working electrode was found to be more stable and sustains for a longer period than that of ZnO/Al working electrode in terms of potassium sensing.